2019
DOI: 10.1186/s13000-019-0896-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid urothelial carcinoma: a rapid autopsy case report with unique clinicopathologic and genomic profile

Abstract: Background Rapid (“warm”) autopsies of patients with advanced metastatic cancer provide important insight into the natural history, pathobiology and histomorphology of disease in treatment-resistant tumors. Plasmacytoid urothelial carcinoma (PUC) is a rare variant of urothelial carcinoma characterized by neoplastic cells morphologically resembling plasma cells. PUC is typically aggressive, high-stage at presentation, and associated with poor outcomes. Recurrence is common in PUC, with the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Half of the PUC cases showed loss of E‐cadherin expression. The IHC analysis of pathological specimens can distinguish PUC from lobular breast and diffuse gastric carcinomas which share a similar morphologic appearance 2,3 . In this case, the authors revealed higher HER2 expression within the autopsy PUC specimen.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Half of the PUC cases showed loss of E‐cadherin expression. The IHC analysis of pathological specimens can distinguish PUC from lobular breast and diffuse gastric carcinomas which share a similar morphologic appearance 2,3 . In this case, the authors revealed higher HER2 expression within the autopsy PUC specimen.…”
mentioning
confidence: 64%
“…Therefore, urologists should be cognizant of the inherent limitations in diagnosing PUC relapse. Patients may require treatment based on symptoms and clinical suspicion 2 . Circulating tumor cells (CTCs) are indicators of recurrence and prognosis for several types of cancers, and can provide information about tumor biology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The current case is the second autopsy report of PUC. 6 Moreover, to the best of our knowledge, this study is the first to assess the CTCs.…”
Section: Discussionmentioning
confidence: 95%
“…PUC may pose a significant diagnostic problem, particularly when it occurs in its exclusively pure or predominant pattern in a limited biopsy, cytology, or transurethral resection specimen. Moreover, reflecting an infiltration pattern arranged as diffuse, thick sheets, cords, or nests of small discohesive tumor cells without forming a focal mass [5], it is challenging to detect PUC via imaging procedures [6,7]. Initial manifestations of PUC may include distant metas-tasis or peritoneal dissemination [8].…”
mentioning
confidence: 99%